Historical Changes in Masik Dharma Practice in Sanatani Young Female: A Study of Sajanpur, Jhapa - Subba Mabuhang, Tanka; Kattel, Anuja (Adhyayan Journal, 2026)
This study examines how young Hindu women in the Sajanpur Municipality, Jhapa, Nepal, between the ages of 17 and 24, are changing their attitudes and behaviors about menstrual taboos. Historically, taboos that have their roots in Hindu traditions consider Masik Dharma to be impure and impose restrictions, including being excluded from temples, kitchens, and social gatherings. But these ideas are changing as a result of globalization, urbanization, education, and modernization. The research used a mixed-method anthropological approach that included questionnaires, focus groups, and interviews with 30 participants, showing that many young women are increasingly rejecting stigmatization, openly discussing Masik Dharma, and adopting modern hygiene practices, even though some taboos still exist for the sake of maintaining family harmony. This shift is facilitated by the media, peer networks, and maternal influence, which promote cultural negotiation between tradition and modernity. Results show that Masik Dharma, which was formerly taboo, is now being discussed openly, suggesting a larger shift in culture.